2015
DOI: 10.1016/j.fertnstert.2014.12.120
|View full text |Cite
|
Sign up to set email alerts
|

Association of number of retrieved oocytes with live birth rate and birth weight: an analysis of 231,815 cycles of in vitro fertilization

Abstract: Objective To determine if number of oocytes correlates with live birth rate and incidence of low birthweight (LBW). Design Retrospective cohort. Setting N/A. Patients Women undergoing fresh embryo transfer utilizing either autologous (n=194,627) or donor (n=37,188) oocytes whose cycles were reported to the Society for Assisted Reproductive Technology 2004–2010. Main outcome measures Live birth rate, birthweight, birth weight z-score, LBW. Interventions None. Results For both autologous and donor oo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
46
2
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(54 citation statements)
references
References 47 publications
5
46
2
1
Order By: Relevance
“…In conception cycles compared to non-conception cycles, higher number of oocytes retrieved, all available embryos, good-quality embryos, blastocysts, freezing surplus blastocysts, proportion of cycles with embryo transfer of at least one good-quality embryo, and lower dose of gonadotrophins were all related to a higher clinical pregnancy rate which is in consistence with findings of other authors [3, 1518]. Women who did not get pregnant were older that those who did, but this difference did not reach statistical significance.…”
Section: Discussionsupporting
confidence: 88%
“…In conception cycles compared to non-conception cycles, higher number of oocytes retrieved, all available embryos, good-quality embryos, blastocysts, freezing surplus blastocysts, proportion of cycles with embryo transfer of at least one good-quality embryo, and lower dose of gonadotrophins were all related to a higher clinical pregnancy rate which is in consistence with findings of other authors [3, 1518]. Women who did not get pregnant were older that those who did, but this difference did not reach statistical significance.…”
Section: Discussionsupporting
confidence: 88%
“…Other factors affecting the endometrium and uterine environment may also be associated with adverse outcomes. Both gonadotropin dose and number of oocytes retrieved are associated with reduced live birth rates and decrements in birthweight (62, 63). …”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have evaluated an association between the number of mature oocytes retrieved and pregnancy outcomes in both autologous and donor IVF cycles respectively (12,1619). Consistent with our findings, Baker et al found that an increasing number of total number of oocytes retrieved was associated with greatest probability of live birth rate in both autologous and donor cycles.…”
Section: Discussionmentioning
confidence: 99%
“…Mirkin et al suggested that a baseline follicle stimulating hormone (FSH) between 4 and 8 IU/L was predictive of IVF outcomes (8). In contrast, Barton et al did not observe an association between FSH levels and LB outcomes (11), and observed that the total number of oocytes retrieved was associated with greatest probability of live birth (12). Following adjustment for oocyte donor age, Cohen et al found that the number of oocytes was not associated with pregnancy outcome (7,12).…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation